ANALYSIS ON THINKING SKILL: COGNITIVE LOAD MANAGEMENT IN CONNECTED INTEGRATED LEARNING - Anna Fitri Hindriana; Handayani Handayani; Ina Setiawati (Jurnal Pengajaran MIPA, 2020)
Connected learning on Plant Structure and Function Couse aims to increase students thinking skills. This integrated learning is needed during information processing when students receiving information with high element interactivity which leads to high level of cognitive load. In other words, this connected integrated learning is necessary to decrease students cognitive load when receiving information. This study, furthermore, utilizes correlational method with 21 students enrolling in Plant Anatomy and Plant Physiology Courses as research subjects. The data collection was completed quantitatively and qualitatively. The qualitative data was collected from students answers in indentifying structure of plant organ while quantitative data was collected from information analysis skill test in form of essay question. The findings show that majority of students have good ability in identifying plant organ structure while their information analysis skill is categorized as very good. Moreover, students feel easiness in receiving information about relation between plant structure and function using connected integrated learning.